2019
DOI: 10.3319/tao.2018.07.09.03
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the melting glaciers in Southeast Tibet by ALOS-PALSAR data

Abstract: Global warming has resulted in the melting of glaciers in the southeastern region of Tibet. This study used the InSAR time series obtained from ALOS PALSAR data to investigate the melting glacier over Southeast Tibet during 2007-2010 with the small baseline subset (SBAS) technique. Additionally, GRACE (Gravity Recovery and Climate Experiment) gravity field model issued by the Center for Space Research (CSR) was used to extract the equivalent water height (EWH) with the deduction of glacial isostatic adjustment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Wang et al (2011) selected five parameters, i.e., mother glacier area, distance between lake and glacier terminus, slope between lake and glacier, mean slope of moraine dam, and mother glacier snout steepness, to identify the first order dangerous glacial lakes in southeastern Tibetan Plateau using Landsat images, ALOS AVNIR-2 and DEM. The recent study have found strong melting and deformation of southeastern Tibetan glaciers using satellite data (Du et al 2019). Wang et al (2012) used five indices (dam type, size of lake, changes in area, dam characteristics and distance between lake and parent glacier) to identify PDGL in the Chinese Himalaya using ASTER images and digitized DEM from topographic maps.…”
Section: A Summary On Remote Sensing Techniques For Identifying Dangementioning
confidence: 99%
“…Wang et al (2011) selected five parameters, i.e., mother glacier area, distance between lake and glacier terminus, slope between lake and glacier, mean slope of moraine dam, and mother glacier snout steepness, to identify the first order dangerous glacial lakes in southeastern Tibetan Plateau using Landsat images, ALOS AVNIR-2 and DEM. The recent study have found strong melting and deformation of southeastern Tibetan glaciers using satellite data (Du et al 2019). Wang et al (2012) used five indices (dam type, size of lake, changes in area, dam characteristics and distance between lake and parent glacier) to identify PDGL in the Chinese Himalaya using ASTER images and digitized DEM from topographic maps.…”
Section: A Summary On Remote Sensing Techniques For Identifying Dangementioning
confidence: 99%
“…The global foF2 and hmF2 maps provided by IZMIRAN can be regarded as new GIM-TEC products [32]. The GIM-TECs are estimated by the dual-frequency observations obtained from hundreds of International GNSS Service (IGS) stations with spherical harmonics and have been widely applied in scientific research and practical productions [33][34][35][36]. Therefore, the IZMIRAN maps were capable of meeting the requirements of this study.…”
Section: Validation Of Accuracy Over the Greenwich Meridianmentioning
confidence: 96%
“…(4) Glacier and landslide dynamics from SAR Du et al (2019) used ALOS_PALSAR images to show the lowering of glacier elevation in southeastern Himalayas, where GRACE shows the largest loss of glacier mass (Fig. 2).…”
Section: (1) Satellite-based Global Gravity Modelmentioning
confidence: 99%
“…Figure 3 shows the coverage of the SAR images over the Himalayas from Sentinel-1A, which is in a 12-day repeat observing cycle. The SAR-related works in this special issue are Du et al (2019), Liu et al (2019), and Tseng et al (2019). With more publicly available SAR images from satellite missions like ESA's Sentinel-1A/-1B, and JAXA's ALOS and ALOS-2, publicly available SAR data processing software systems such as GMTSAR and others, SAR estimates of glacier melt rate, landslide and surface deformation in Tibet have been demonstrated.…”
mentioning
confidence: 99%